Analisis Uji Keserempakan Pemutus Tenaga 150kv Bay Trafo-1 Gardu Induk 150kv Tasikmalaya Baru - surya sasana; Ibrahim ,; Reni Rahmadewi (Jurnal Ilmiah Wahana Pendidikan, 2023)
High voltage substation is a crucial facility in the electric power system. This facility functions to distribute electricity from power plants to consumers through complex equipment such as transformers, switches and circuit breakers. The goal is to ensure a stable and secure supply of electricity. One of the important devices in a substation is the Power Disconnector (PMT), whose job is to cut off the flow of electricity in the event of a disturbance or overload on the electrical network. PMT has an important role in maintaining the security and availability of electricity supply in the power grid. Therefore, damage to PMT is very detrimental to the operation of the electric power system, so it is necessary to test it regularly to ensure its safety and controllability in operation. In this study, the simultaneity test was only carried out, namely by comparing the values obtained with the standard values for each test listed in SK-DIR 0520-2014. The test results show that the delta time values obtained both at open and close are each under 10ms, so it can be concluded that the PMT installed in transformer bay-1 of the Tasikmalaya Baru 150kv substation is still in safe condition and feasible to operate according to standards.